Discussion: Activation volumes of plastic deformation of crystals - Blum, Wolfgang (Scripta Materialia, 2018)
Two data sets reporting apparent activation volumes V-app of plastic deformation of ultrafine-grained Cu are compared. They differ strongly in magnitude and stress dependence of Vapp. It is suggested that the difference results from differences in testing method. While Vapp from stress relaxations appears to be consistent with expectations for the activation of thermally activated glide of dislocations in the bulk of the material, Vapp from rate change tests appears to characterize the quasi-stationary deformation where dynamic recovery plays a major role. This underscores the necessity to specify which of the various thermally activated subprocesses of deformation are tested. (C) 2017 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.